DIFFERENCES OF INTERLEUKIN-18 AND INTERLEUKIN-10 LEVELS IN RIFAMPICIN RESISTANT AND RIFAMPICIN SENSITIVE PULMONARY TUBERCULOSIS PATIENTS IN DR. SOETOMO HOSPITAL SURABAYA - Riwu, Audrey Gracelia; Nugaraha, Jusak; Dachlan, Yoes Prijatna (Institute of Topical Disease Universitas Airlangga, 2020)
Rifampicin is an anti-tuberculosis drug which has an efficient antimicrobial effect and the basis of a short-term treatment regimen for tuberculosis (TB) patients. Rifampicin plays an important role against the growth and slow metabolism of Bacilli M. tuberculosis. Resistance to rifampicin causes the duration of tuberculosis treatment to be longer. Interleukin-18 (IL-18) is a pro-inflammatory cytokine which plays a role in controlling the growth of M. tuberculosis through its ability to induce IFN-Î³, while Interleukin-10 (IL-10) is an anti-inflammatory cytokine which plays a role in limiting tissue damage due to the inflammatory process and maintain tissue homeostasis. IL-18 and IL-10 has an important role in explaining the different degrees of inflammation in rifampicin resistant (RR) and rifampicin sensitive (RS) pulmonary tuberculosis patients. The purpose of this study is to determine different levels of IL-18 and IL-10 in new TB patients with RR and RS. This study was a retrospective cohort study with a cross-sectional design carried out from August-November 2018 in the TB-DOTS/MDR clinic at Dr. Soetomo Hospital, Surabaya. 50 research subjects were examined and grouped into two groups, namely pulmonary TB with RR (n = 25) and pulmonary TB with RS (n = 25) based on GeneXpert examination and anti-tuberculosis drug therapy â‰¤ 1 month. IL-18 and IL-10 were measured using the ELISA Method. Differences in IL-18 and IL-10 levels between groups were analyzed using the Mann-Whitney test. The mean level of IL-18 (pg/ml) in RR and RS pulmonary TB patients were 1273.53±749.86 and 787.96 ±589.28 respectively. The mean level of IL-10 (pg/ml) in RR and RS pulmonary TB patients were 125.25±118.32 and 128.81±135.77 repectively. The mean level of IL-18 in RR and RS pulmonary TB patients were found to have a significant difference, while the mean level of IL-10 did not have a significant difference. Keywords: Interleukin-18, Interleukin-10, Tuberculosis, Rifampicin Resistant, Rifampicin Sensitive